Quality of Chocolate Bar from Fermented Cocoa Beans from Lombok, West Nusa Tenggara. (March 2019) - Fahrurrozi; Fauziyyah, S; Sari, M N; Ratnakomala, S; Lisdiyanti, P
Abstract: About 500 kgs cocoa beans have been fermented using box fermentation. The fermentation experiments were conducted at the Gangga district North Lombok, West Nusa Tenggara - Indonesia. The starter culture, which contains yeast, lactic acid bacteria, and acetic acid bacteria (10 7 /mL) was added to cocoa beans mass in box fermentation. The fermentation was conducted for 5 days and every 24 hours were mixed. After fermentation, the cocoa beans were dried for 5 days to reduce the moisture content using a sun drying. Dried fermented cocoa beans were processed to be a chocolate bar. The quality of cocoa liquor was determined using organoleptic score. Chocolate aroma, chocolate flavour, and caramelly score were 8.25. The texture and colour score were 8.00 and off flavours score was 0.00. Overall quality of cocoa liquor score was excellent. Analysis of proximate and microbiological properties was carried out to obtain the chocolate bar qualities. The result showed that quality of chocolate bar from fermented cocoa beans appropriate with SNI 7934:2014 about chocolate and chocolate products.